Analisis Perubahan Desain Gedung Pada Tahap Konstruksi Terhadap Perhitungan Volume dan Bill of Quantity (BoQ) - Rivana, Dila; Farhani, Shyva; Tanne, Yongki Alexander (Jurnal Manajemen Teknologi & Teknik Sipil, 2024)
Construction design changes are a challenge that requires quick adjustments in project documents, especially in the Bill of Quantity (BoQ). These adjustments reflect major changes in costs and material requirements. The use of digital technology is key to facilitating this process, enabling faster and more accurate revisions. This research aims to compare volume calculations using Revit and manual volume calculations resulting from design changes in the YOGYA Kota Baru Parahyangan Development Project. In the process, the volume of material required for various construction elements is calculated manually and with the help of digital technology. The results of these two methods were then compared to determine significant differences and evaluate each method's efficiency and accuracy. This results show that the volume difference in profile steel profiles is +47.78%; concrete +21.83%; piles +12.06%; and reinforcement +2.00%. These findings show that Revit provides more accurate and detailed results than manual calculations, which are often prone to human error. Using Revit can speed up the design adjustment process, reduce costs and project completion time. This research contributes by providing empirical evidence of the benefits of digital technology in construction and practical guidance for professionals in choosing the right calculation method.